Diastereoselective Double C−H Functionalization of Chiral Ferrocenes with Heteroaromatics. Issue 62 (5th October 2021) - Plevová, Kristína; Kisszékelyi, Péter; Vargová, Denisa; Andrejčák, Samuel; Tóth, Viktor; Fertáľ, Lukáš; Rakovský, Erik; Filo, Juraj; Šebesta, Radovan
Abstract: Diastereoselective double C−H heteroarylation of chiral ferrocenes provides valuable compounds with multiple functionalities using mild reaction conditions and simple reagents. Pd‐Complexes with chiral mono‐protected amino acids afforded corresponding heteroarylated ferrocenyl amines in good yields and high diastereomeric purities. In this way, a variety of indole, thiophene, pyrrole, or furan substituents were introduced to the ferrocene moiety. Furthermore, a range of relevant functional groups, for example ketone, ester, chloro, nitro, or silyl, are tolerated by this method. An alternative combination of amino acid and ferrocenyl amine configurations was leveraged to provide the complementary diastereomeric products. The products of C−H heteroarylation can be transformed into corresponding phosphines. Absolute configurations of CH‐activation products were confirmed by the combination of X‐ray crystallographic analysis and CD spectroscopy. 19 F NMR kinetic study and DFT calculations provided insights into the reaction mechanism and reasons governing stereoinduction. Abstract : Pd‐Complexes with N ‐Boc protected amino acids catalyze diastereoselective oxidative double C−H functionalization of chiral ferrocenyl amines with heteroarenes. A range of thiophene, pyrrole, furan and indole ferrocene derivative can be obtained in a single step and in high diastereomeric purities. C−H activation products can be transformed to corresponding phosphines. 19 F NMR and DFT calculations helped elucidate reaction mechanism and reasons for stereoinduction.